KECERNAAN NUTRIEN SECARA IN VITRO PADA FODDER JAGUNG HIDROPONIK DENGAN MEDIA PERENDAMAN DAN PENGGUNAAN DOSIS PUPUK YANG BERBEDA (The In Vitro Nutrient Digestibility of Hydroponic Maize Fodder with Different Soaking Medium and Fertilizer Doses) - A. D. Riswara; L. K. Nuswantara; J. Achmadi (Jurnal Ilmu dan Teknologi Peternakan, 2018)
The study was aimed to clarify interactive effect between the soaking medium and fertilizer doses on in vitro nutrient digestibility of hydroponic fodder maize. The first factor included M0 (without soaking H2SO4) and M1 (soaking H2SO4). The second factor included N0 (0 gram), N1 (0.5 gram) and N2 (1 gram) of fertilizer/liter water. The research design was 2 x 3 factorial with 3 replicates. Results of this study showed that the interactive treatments significantly increased (P<0.05) the digestibilities of dry matter, organic matter, and crude protein of maize fodder. The treatment of M1N1 produced the highest dry matter and organic matter digestibilities. The treatment of M1N2 gave the highest crude protein digestibility.